Respuesta :
Answer: 27
Step-by-step explanation:
- Set the age of the person who entered the room as x
[tex]Mean=\frac{16 + 25 + 23 + 12 + 17 + x}{6}=20 \\16 + 25 + 23 + 12 + 17 + x=20(6)\\93+x=120\\x=120-93=27[/tex]
Answer:
27 years old
Step-by-step explanation:
There are originally 5 people in the room.
Their ages are: 16, 25, 23, 12, 17
The sum of their ages is: 93
One person enters the room. That person's age is unknown, so we call it x.
The sum of the ages of the 6 people is:
x + 93
There are 6 people in the room now, so the mean age is (total age divided by number of people):
(x + 93)/6
We are told the mean age is 20.
(x + 93)/6 = 20
x + 93 = 120
x = 27
Answer: 27 years old